Pengaruh Amplitudo Ultrasonik dan Waktu Ekstraksi Terhadap Rendemen dan Mutu Oleoresin Pala - I Wayan Budiastra; Sutrisno Suro Mardjan; Ahmuhardi Abdul Azis (Jurnal Keteknikan Pertanian, 2020)
Nutmeg oleoresin is one of the nutmeg derivative products with high values produced from the extraction process. The conventional extraction process using maceration takes a long time so that it is less suitable for industries needs. This study aims to examine the UAE direct sonication method for increasing yield and quality of nutmeg eleoresin. Nutmeg with optimal maturity level were harvested, dried and milled into 60 mesh particle size. Nutmeg powder of 200 g was placed in beaker glass filled with etanol 800 ml (material and solvent ratio 1:4) and UAE was carried out using a sonicator with a frequency of 20 kHz and power of 700 W. Four ultrasound amplitude levels (45, 60, 75, 90%) and four levels of extraction time (30, 45, 60, 75 minutes) were taken as UAE treatments. Extraction using maceration at room temperature for 7 hours was done as control.  The results showed that the greater the amplitude of the ultrasound, the higher the yield of nutmeg oleoresin. The longer the extraction time, the higher the yield of nutmeg oleoresin. Ultrasonic assisted extraction can increase nutmeg oleoresin yield by 11 to 52% and faster time (<= 1,25 hour) than maceration extraction method (7 hours).